Bachmann's Bundle Versus Right Atrial Appendage Pacing: A Systematic Review and Meta‐Analysis - Raam Mannam; Ravi Medarametla; Sunil Bogati; Kaushal Patel; Nirmit Patel; Gaurav Patel; Ashok Runkana; Atul Prakash (Pacing and Clinical Electrophysiology, 2026)
ABSTRACT Background Right atrial appendage (RAA) pacing remains the default atrial lead position despite evidence that non‐physiological atrial activation promotes interatrial dyssynchrony. Bachmann's bundle pacing (BBp) targets the interatrial conduction pathway. We evaluated whether BBp improves electrophysiologic markers of atrial synchrony and whether this is accompanied by a reduction in atrial fibrillation (AF) incidence compared with RAA pacing. Methods Systematic review and meta‐analysis of studies comparing BBp with RAA pacing. PubMed, Embase, Scopus, Cochrane Library, ClinicalTrials.gov, and reference lists were searched (December 2025). Primary outcome: P‐wave duration change. Secondary: AF incidence. Safety: lead dislodgement. Random‐effects (REML) models. Results Eight studies comprising 731 patients were analyzed. BBp was associated with a consistent reduction in P‐wave duration (primary analysis, 5 independent‐group studies: MD −34.61 ms; 95% CI −39.84 to −29.38; p < 0.001; I 2 = 0%; 6‐study sensitivity including Vedage et al.: MD −35.24 ms; I 2 = 0%), indicating a shortening of global atrial activation time. BBp was also associated with a lower AF incidence across three RCTs (RR 0.59; 95% CI 0.37–0.94; p = 0.026); however, this estimate was imprecise and sensitive to removal of the dominant contributing trial. Atrial lead dislodgement was rare and events were insufficient for formal pooled analysis; no excess dislodgement signal was observed, but comparative safety remains uncertain given event sparsity. Conclusions BBp consistently reduced P‐wave duration across diverse paced populations and generated a fragile signal toward lower AF incidence. Comparative lead safety is uncertain due to sparse events. These findings support investigation in prospective trials but do not justify immediate practice change. PROSPERO Registration CRD420261282981.